Respuesta :

ayune

Given an arithmetic sequence -2,-13,-24, . . . , the recursive formula is: a(n) = a(n-1) -11 and the explicit formula is a(n) = 9 - 11n

Suppose we are given an arithmetic sequence:

  a(1), a(2), a(3), a(4), ....

Then, in an arithmetic sequence, the next term is obtained by adding a constant to the previous term. This constant is called a common difference.

Let d = common difference, then
a(2) = a(1) + d

a(3) = a(2) + d

and so on, until

a(n) = a(n-1) + d

This is a recursive formula. Here a(n) = nth term, and a(n-1) = (n-1)th term.

The sequence in the problem:

       -2,-13,-24, . .

Notice that:

-13 = -2 + (-11)

-24 = -13 + ( -11)

Hence, d = -11, and therefore, the recursive formula for the nth term is:

a(n) = a(n-1) -11

To find the nth term, we can also use the explicit formula:

a(n) = a(1) + (n-1).d

In the given sequence, a(1) = -2, and d = -11. Substitute these parameters:

a(n) = -2 + (n-1) . (-11)

      = -2 - 11n + 11

      = 9 - 11n

Thus, the explicit formula is a(n) = 9 - 11n.

Learn more about arithmetic sequences here:

https://brainly.com/question/2333529

#SPJ4